GAMBARAN TINGKAT PENGETAHUAN TENTANG PENCEGAHAN COVID-19 BERDASARKAN KARAKTERISTIK MASYARAKAT DI KOTA ADMINISTRASI JAKARTA TIMUR - Shafa Mutiara Afifah; Mateus Sakundarno Adi; Mohammad Arie Wuryanto; Lintang Dian Saraswati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Coronavirus disease 2019 (COVID-19) can be prevented by implementing clean and healthy living behavior and obeying health protocols. East Jakarta City was the city with the highest COVID-19 confirmed cases (as of May 13, 2020). The purpose of this study is to describe knowledge about COVID-19 prevention in the community of East Jakarta city based on gender, education level, and the history of chronic disease. This study used a cross-sectional study design and quota sampling as a sampling technique with a sample size of 480 respondents and data was collected by using self-reported questionnaire via Google Form. The results showed that 52.5% of the respondents had good knowledge of COVID-19 prevention, indicated in detail by 58.4% of men, 53,2% of respondents with high education level and 61.5% of respondents with chronic disease. In conclusion, East Jakarta community has good knowledge of COVID-19 prevention. Interactive and focused COVID-19 prevention promotion in public is needed to improve a certain population knowledge.